AUTONOMOUS RAIL RAPID TRANSIT: INOVASI TRANSPORTASI MODERN UNTUK MENGATASI KENDALA-KENDALA KONVENSIONAL DI KOTA BESAR INDONESIA - sitorus, budi (JURNAL KEBIJAKAN PUBLIK, 2024)
The rapid development of big cities in Indonesia encourages economic growth that has an impact on the urbanization of big cities, as a reason for people to choose a place to live and find jobs. The problem of urbanization is that it requires mobility. The need for urban mobility is caused by conventional transportation conditions that currently often experience delays and overcapacity, dense population growth in big cities and less regular traffic in big cities. Autonomous Rail Rapid Transit (ART) being a novelty in transportation in Indonesia, the operation of autonomous trains began in the Ibu Kota Nusantara. Autonomous trains are capable of transforming urban travel in the future. Using autonomous technology and advanced sensors, trains can operate without human control, unlocking the potential for increased efficiency, safety and comfort in rail transport systems. The research problem is to determine policy alternatives in legal and regulatory aspects such as the level of autonomy, testing and certification, licensing and licensing, legal responsibility, data security, communication and interoperability standards, security checks and education and public awareness. The research method uses a descriptive qualitative approach, with secondary data collection and the use of problem trees. The results show that Autonomous Rail Rapid Transit (ART) offers a future of safe, efficient and accessible mobility. The implementation of ART in Indonesia requires the collaboration of government, industry, education, and society to overcome technical, regulatory, and socio-cultural challenges.